2019
DOI: 10.1161/circinterventions.118.006071
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Management of Out of Hospital Cardiac Arrest

Abstract: Out of hospital cardiac arrest (OHCA) is a major cause of morbidity and mortality worldwide. Clinical decision making is extremely difficult in this understudied patient population with high prevalence of neurological injury and inexorable shock states. As such, there are uncertain benefits from therapies available in the cardiac catheterization laboratory. Fear of futility and public reporting often affects decision making and can result in risk aversion. This review focuses on invasive management in OHCA car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Sudden cardiac death (SCD) is an emergent medical condition that requires timely intervention to bring the victim back to life [ 1 , 2 ]. However, since all SCD cases occur outside the hospital, immediate professional intervention is virtually impossible [ 2 , 3 , 4 , 5 ]. The SCD survival rates are still not satisfactory, even in the most developed regions of the world, whereas neurologically intact survival rates are even lower [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sudden cardiac death (SCD) is an emergent medical condition that requires timely intervention to bring the victim back to life [ 1 , 2 ]. However, since all SCD cases occur outside the hospital, immediate professional intervention is virtually impossible [ 2 , 3 , 4 , 5 ]. The SCD survival rates are still not satisfactory, even in the most developed regions of the world, whereas neurologically intact survival rates are even lower [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying causes of SCD include coronary artery disease, primary myocardial or electrical disorders such as hypertrophic cardiomyopathy and Brugada syndrome, and valvular heart disease [ 3 , 8 ]. Metabolic syndrome, which is characterized by abdominal obesity, dyslipidemia, an elevated fasting glucose, and high blood pressure, is an established risk factor for coronary artery disease and SCD [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…PCPS was used aggressively in patients who could not be resuscitated successfully. Several studies have shown the benefit of extracorporeal cardiopulmonary resuscitation (CPR) in CA patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the pooled incidence of return of spontaneous circulation (ROSC) is 29.7%, only 8.8% achieved 30-day survival globally ( 3 ) and 5.8% in the Asia Pacific ( 4 ). Advanced interventions post-ROSC can improve mortality in well-selected patients, ( 5 ) but also come with significant costs estimated at USD 333,844 per person ( 6 ).…”
Section: Introductionmentioning
confidence: 99%